1988
DOI: 10.1063/1.341744
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and thermoelectrical properties of Zn3P2 films grown by the hot wall epitaxy technique

Abstract: Zinc phosphide thin films were prepared by the hot wall epitaxy technique. The transport properties of films grown at different substrate temperatures from 200 to 350 °C were studied from room temperature up to 600 °C. Films were also grown in pure oxygen and nitrogen atmospheres at a pressure of 10−6 Torr, and the conductivity of the films was measured in situ. Thermoelectric measurements on films grown on mica were also done at various temperatures ranging from 300 to 800 K. Arrhenius plots of electrical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Although the energy barrier at the interfacial layers in these nanowire pellets could be calculated given carrier mobility measurements as a function of temperature for each pellet as given by Seto [44], the low electrical conductivity of the undoped samples [44,45] prevented the generation of a coherent mobility plot for testing the carrier filtering hypothesis. Overall, the thermoelectric power factors of both unfunctionalized and BDT functionalized Zn 3 P 2 nanowire pellets (figure 5(c)) are higher than those reported for bulk Zn 3 P 2 by Babu et al [46]. Also, the overall thermoelectric performance of BDT functionalized nanowires is on par with that observed in Zn 3 P 2 microparticles by Nagamoto et al…”
Section: Electrical Transport Propertiesmentioning
confidence: 61%
“…Although the energy barrier at the interfacial layers in these nanowire pellets could be calculated given carrier mobility measurements as a function of temperature for each pellet as given by Seto [44], the low electrical conductivity of the undoped samples [44,45] prevented the generation of a coherent mobility plot for testing the carrier filtering hypothesis. Overall, the thermoelectric power factors of both unfunctionalized and BDT functionalized Zn 3 P 2 nanowire pellets (figure 5(c)) are higher than those reported for bulk Zn 3 P 2 by Babu et al [46]. Also, the overall thermoelectric performance of BDT functionalized nanowires is on par with that observed in Zn 3 P 2 microparticles by Nagamoto et al…”
Section: Electrical Transport Propertiesmentioning
confidence: 61%
“…Although there have been numerous reports on the optoelectronic properties of this compound [10,12,22e24], stemming from its use in photovoltaic (PV) devices, there are relatively few studies which report on the thermal properties. With previous studies having reported large Seebeck coefficients [15,20,21e25] (1.8 mV/K at room temperature reported by Babu et al [25]) and no appreciable changes to the electrical conductivity in the presence of grain boundaries [22e25], further reductions of the lattice thermal conductivity through nanostructuring could be beneficial to increasing the viability of this compound for use in thermoelectric applications. In this work the thermal conductivity of Zn 3 P 2 thin films with crystallite sizes less than 10 nm is presented.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies have demonstrated that k p in Zn 3 P 2 can be dramatically reduced by nanostructuring, even below the predicted k min , and that r is not affected by the crystallinity in Zn 3 P 2 thin films. 37,38 Herein, we present that the low thermal conductivity in Zn 3 P 2 can be delineated with the phonon dispersion curve using no fitting parameters. Most of the published studies, however, reported the electronic or thermal properties only in a small temperature range and coherent data are necessary to avoid discrepancy between samples.…”
Section: Introductionmentioning
confidence: 99%